Antibodies against Clostridium butyricum in the children of mothers at risk for gestational diabetes - Peterson, Celeste; Tagoma, Aili; Alnek, Kristi; Bärenson, Anu; Vorobjova, Tamara; Talja, Ija; Janson, Helis; Kirss, Anne; Kõljalg, Siiri; Sinkkonen, Aki; Roslund, Marja Irmeli; Uibo, Raivo; et al. (Informa UK Limited, 2025)
Gestational diabetes mellitus (GDM) is linked to an imbalance in gut microbiota composition, which can be transferred to the mother’s offspring. Clostridium butyricum, known for its health benefits in diabetes and allergy, lacks sufficient data regarding its effect on the immune system’s development in the offspring of mothers with GDM. This study assessed antibody responses against C. butyricum T2F3 in children of mothers at risk for GDM, involving 88 children aged 1–6 years. Antibody responses were measured with flow cytometry and immunoblot. Lower IgG median fluorescence intensity (MFI) values and fewer IgA and IgG bands against C. butyricum were detected in children of mothers with GDM. Maternal body mass index was positively associated with children’s IgG MFI and number of IgG bands. Fewer IgA bands were detected in children with higher IgE levels, atopic dermatitis, asthma, and allergic rhinitis. More IgG bands were detected in children with higher anti-β-lactoglobulin IgG levels. Children with autoimmune risk-related HLA-DR3/DQ2.5 had fewer IgA bands, while those with neutral HLA-DR1/DQ5 had higher IgA, but lower IgG MFI. These results indicate that maternal prenatal changes could affect their offspring’s immune response against C. butyricum. Moreover, C. butyricum could have a protective role against allergic sensitization.
Keywords: Clostridium butyricum; gestational diabetesmellitus; atopicdermatitis; asthma; antibody